Faith-Based Initiatives in Health Promotion: History, Challenges, and Current Partnerships. Issue 3 (January 2014) - Levin, Jeff
Faith-based institutions and organizations represent a longstanding yet underutilized resource for health promotion and disease prevention efforts. The White House Office of Faith-Based and Neighborhood Partnerships, and its affiliated office within the Department of Health and Human Services, are the highest-profile markers of federal efforts, but most faith-health partnerships are not federally funded and date back many decades. Formal partnerships between the faith-based and public health sectors encompass activities in the fields of health behavior and health education, health policy and management, epidemiology and biostatistics, and environmental health. These partnerships are instrumental for achieving both domestic and global health promotion priorities.